2008
DOI: 10.1111/j.1467-9566.2008.01092.x
|View full text |Cite
|
Sign up to set email alerts
|

From Lydia Pinkham to Queen Levitra: direct‐to‐consumer advertising and medicalisation

Abstract: The medicalisation of life problems has been occurring for well over a century and has increased over the past 30 years, with the engines of medicalisation shifting to biotechnology, managed care, and consumers. This paper examines one strand of medicalisation during the last century: direct-to-consumer advertising (DTCA) of pharmaceuticals. In particular, it examines the roles that physicians and the Food and Drug Administration (FDA) have played in regulating DTCA in the US. Two advertising exemplars, the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…However, the US regulations on 'fair balance' and 'brief summary' made DTCA cumbersome for the broadcast media. In 1997, by which time the pharmaceutical industry had become firm supporters of DTCA, even those restrictions were relaxed so that broadcasting product advertisements merely had to provide consumers with access to the drug's official labelling via a telephone number, a webpage, a concurrent advertisement, or additional information from pharmacists, physicians or other healthcare providers (Conrad and Leiter 2008). The consequence of these deregulatory measures in 1985 and 1997 was that expenditure on broadcast DTCA, a form of prescription-drug promotion which bypassed doctors, grew almost 80-fold in the US, from US$55 million in 1991 to US$4.2 billion in 2005(UG GAO 2006.…”
Section: Consumerism and The Patient-industry Complexmentioning
confidence: 99%
“…However, the US regulations on 'fair balance' and 'brief summary' made DTCA cumbersome for the broadcast media. In 1997, by which time the pharmaceutical industry had become firm supporters of DTCA, even those restrictions were relaxed so that broadcasting product advertisements merely had to provide consumers with access to the drug's official labelling via a telephone number, a webpage, a concurrent advertisement, or additional information from pharmacists, physicians or other healthcare providers (Conrad and Leiter 2008). The consequence of these deregulatory measures in 1985 and 1997 was that expenditure on broadcast DTCA, a form of prescription-drug promotion which bypassed doctors, grew almost 80-fold in the US, from US$55 million in 1991 to US$4.2 billion in 2005(UG GAO 2006.…”
Section: Consumerism and The Patient-industry Complexmentioning
confidence: 99%
“…In addition, the pharmaceutical industry places understandably more emphasis on promoting information about marketed products than those unable to meet FDA safety and efficacy benchmarks. Within social science and biomedical communities, scholarship has also centered on marketed pharmaceuticals, analyzing physicians’ relationships with industry, direct-to-consumer advertising, and industry constructions of illness (e.g., Conrad & Leiter, 2008; Dumit, 2012; Greene, 2007; Kassirer, 2005). This literature often mobilizes the concept of “pharmaceuticalization” to signal the increasing power of the pharmaceutical industry to shape physicians’ and patients’ engagement with health and illness (Abraham, 2010; Bell & Figert, 2012; Busfield, 2010; Williams, Gabe, and Davis, 2008; Williams et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Salonia et al 22 reported on 619 patients seeking medical help for new-onset ED in the PDE5i era, where the mean delay prior to presentation was 30.2 months (median 12.0; range 5-300). This delay seems surprising given the likely waning of the taboo associated with openly discussing ED, as well as the explosion of direct-to-consumer advertising for ED treatments in both electronic and print media 25 . In another study comprising a cohort of men who underwent PPI, the mean duration of ED prior to surgery was 60 months 23 .…”
Section: Discussionmentioning
confidence: 97%